2016
DOI: 10.14218/jcth.2016.00042
|View full text |Cite
|
Sign up to set email alerts
|

Massive Hemolysis Causing Renal Failure in Acute Hepatitis E Infection

Abstract: Acute viral hepatitis is usually a self-limiting illness. However, it can lead to complications that can be life-threatening, such as acute liver failure. Glucose 6 phosphate dehydrogenase (G6PD) deficiency in the setting of acute viral hepatitis can lead to a massive hemolysis, manifesting as acute kidney injury and markedly raised bilirubin levels; although cases are rare. Here, we report such a case. The patient had a viral hepatitis E infection and presented with kidney injury requiring dialysis. Examinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…Cases of hemolysis and subsequent renal failure are reported with HEV infection. Karki et al [ 30 ] reported a case of massive hemolysis in a patient with glucose-6-phosphate dehydrogenase (G6PD) deficiency, heme pigment causing direct proximal tubular toxicity. Development of hemoglobin cast further leads to intratubular obstruction and subsequent development of acute kidney injury.…”
Section: Renal Manifestations Of Hev Infectionmentioning
confidence: 99%
“…Cases of hemolysis and subsequent renal failure are reported with HEV infection. Karki et al [ 30 ] reported a case of massive hemolysis in a patient with glucose-6-phosphate dehydrogenase (G6PD) deficiency, heme pigment causing direct proximal tubular toxicity. Development of hemoglobin cast further leads to intratubular obstruction and subsequent development of acute kidney injury.…”
Section: Renal Manifestations Of Hev Infectionmentioning
confidence: 99%
“…Regarding HEV-1 infection, the link between viral infection and acute kidney injury (AKI) and/or KFTs is not clear. Karki et al reported a case of acute HEV infection associated with hemolysis and kidney injury, which required renal dialysis [ 28 ]. Nayak et al reported a case of acute HEV infection that was complicated by cholemic nephrosis (bile cast nephropathy), which could lead to AKI [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…HEV-1 replicates in primary proximal epithelial cells, and HEV RNA and HEV protein increase over time; the infection activates the inflammatory cytokines IL-8 and IL-6, but not chemokine transcripts or kidney injury markers [ 27 ]. In India, where HEV-1 is a common genotype, several HEV-infected cases were found to be complicated by renal failure or cholemic nephrosis [ 28 , 29 ]. In Egypt, HEV-1 is the most commonly reported strain associated with acute hepatitis and fulminant hepatic failure [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to acute and chronic hepatitis, HEV infection is associated with several extrahepatic manifestations, including anemia [ 117 ]. Most cases of anemia during HEV infection are due to hemolysis secondary to glucose-6-phospate dehydrogenase deficit [ 118 , 119 , 120 , 121 , 122 , 123 , 124 ]. However, a few cases of AIHA have been described both in adults and children [ 125 , 126 , 127 ].…”
Section: Hepatic and Gastrointestinal Disorders Predisposing To Aumentioning
confidence: 99%